Cytological and histopathological correlations of the Bethesda 3 categories in thyroid cytopathology: A 4-year single-center experience (Annals of Medical Research, 2025)
Aim: This study aimed to investigate the correlation between thyroid fine needle aspiration biopsy (FNAB) and thyroidectomy materials diagnosed as atypia of undetermined significance (AUS) with histopathological diagnoses over the last four years at our hospital.Materials and Methods: This retrospective study included 251 thyroid FNAB cases with an AUS diagnosis referred to our laboratory between January 1, 2020, and December 31, 2023, and 133 of these patients who subsequently underwent surgery at our hospital.Results: A histopathological diagnosis was made in 133 cases. Ninety-four patients were diagnosed after the first AUS diagnosis, and 39 after at least one control aspiration. Of the 39 patients who underwent a second cytological control, 56.4%(n=22) were diagnosed again with AUS. Of the surgical patients, 36.8%(n=49) were diagnosed with papillary microcarcinoma, 33.83%(n=45) with papillary carcinomas, 9.02%(n=12) with adenomatous hyperplasia and nodular hyperplasia, 6.7%(n=9) with invasive encapsulated follicular variant of papillary thyroid carcinoma, 3.75%(n=5) with follicular carcinoma, 3%(n=4) with chronic lymphocytic thyroiditis, 2%(n=3) with follicular adenoma, 1.5%(n=2) with well differentiated thyroid tumor of uncertain malignant potential, and 0.75%(n=1) each with medullary carcinoma, oncocytic carcinoma, anaplastic carcinoma-not otherwise specified, and paraganglioma.Because the majority (91.83%) of the cases diagnosed with papillary microcarcinoma were ≤5 mm in size, and there were benign nodular structures in non-tumor areas, aspiration was performed from benign nodules, and postoperative papillary microcarcinoma was detected incidentally.Conclusion: In our study, most of the patients diagnosed with AUS had a diagnostic operation by the clinician, and the patients who underwent repeat cytology were mostly persistently diagnosed with AUS. It was remarkable that the majority (36.8%) of the patients diagnosed with AUS from an FNAB were diagnosed with incidental papillary microcarcinoma after resection. Since papillary microcarcinoma tumors are smaller than 1 cm, these cells are not sufficiently included in the cytology material from an FNAB.
Keywords: Histopathology; FNAB; Atypia of uncertain significance; Thyroid